«FREE» AND «BOUND» ANTIBODIES AGAINST HIV–1 STRUCTURE PROTEINS AT EARLY STAGE OF THE DISEASE - G. A. Rjazanova (SPb RAACI, 2014)
Abstract. Using ELISA and immunoblotting we have monitored the activity of “free” antibodies against virus structure proteins in the sera of HIV–infected patients at the stage of the developing humoral immune response. Further, a comparative assessment of “free” and “bound” antibodies frequencies in the sera of HIV–infection patients at early stage of the disease has been made. We have obtained two fractions of circulating immune complex (CIC1 and CIC2) using precipitation in polyethylenglycol.We have determined, that antibodies against virus proteins coded by gag, pot and env genes formed immune complex dissociating under +60°C.Using non parametric criterion for z–signs. We have shown significant differences between the frequency on antibodies against virus structure proteins in sera and the presence of these antibodies in immune complexes. (Med. Immunol., 2005, vol.7, № 1, pp. 73576)